Nurse-led intervention on knowledge, attitude and beliefs towards acute coronary syndrome - Darsin Singh, Sukhbeer K.; Ahmad, Aini; Rahmat, Norsiah; Hmwe, Nant Thin Thin (Wiley, 2016)
Background: Coronary heart disease has emerged as a number one killer in Malaysia and globally. Much of the morbidity and mortality in acute coronary syndrome patients is because of patients not recognizing their symptoms which contributes to delay in seeking early treatment. Aim: The aim of this study is to evaluate the effectiveness of a nurse-led health education programme on knowledge, attitude and beliefs of coronary patients towards the responses to acute coronary syndrome and the association with patients' characteristics. Methods: A single-group quasi-experimental design took place in a tertiary hospital. A total of 60 coronary patients were recruited to this study. The knowledge, attitude and beliefs towards acute coronary syndrome (ACS) were evaluated at baseline and after 1 month of giving education intervention. Results: Knowledge, attitude and beliefs about ACS increased significantly from baseline to 1 month after intervention. Level of attitude was associated with gender, educational level and employment status. Conclusions: The findings of this study suggest that an education program conducted by a nurse improved patients' level of knowledge, attitudes and beliefs in response to ACS symptoms at 1 month compared to baseline, but whether they are sustained for a longer period is unclear. Improving the responses towards ACS might reduce decision delay in symptom interpretation and seeking early treatment. Relevance to clinical practice: Nurse-led interventions have imparted positive outcomes in response to ACS symptoms among coronary patients. Therefore, nurses should take the initiative in educating patients to minimize delay in symptom interpretation and seeking early treatment.